HAK DAN KEWAJIBAN ORANG TUA TERHADAP ANAK AKIBAT ADANYA PERCERAIAN (SUATU KASUS DI PN DENPASAR) - Wiyasa, I Made; Artadi, I Ketut; Ari Krisnawati, I Gusti Ayu Agung (Kertha Wicara : Journal Ilmu Hukum, 2014)
In essence , it means eternal marriage continues, lifetime and should not be decided just like that or dissolved according to the will of the parties . Do not know the eternal marriage period and timeless . Although Law No. . 1 of 1974 on Marriage Divorce is difficult , but in fact the people that divorce is rampant and likely to increase in each year . Social and humanitarian impact caused by a divorce very large , especially for children and women who experience it and for the life of the nation in general . The breakdown of marriage or divorce will result in not only a change in the rights and obligations of the husband and wife , but also the rights and obligations to the child . The rights and obligations of parents of children of divorce are more priority to the interests of the child that such child is entitled to maintenance , education , and the costs of the overall life of the parents . About child custody collectively result of divorce , Law No. . 1 of 1974 or Regulation Legislation does not set out clear , joint custody was only based on the agreement between the plaintiff by the defendant , whether expressed orally or in writing . In order to avoid later konflk the deal should be made authentic certificate .
Keywords: Marriage , Parents , Children , Divorce